Alternatif Penyelesaian Sengketa Kelalaian Medik yang Berkeadilan di Indonesia - Deri Mulyadi (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2020)
The research objective is to analyze medical negligence dispute settlement in Indonesia by litigation (criminal and civil) and non-litigation. The research method is normative juridical. The results of the study are non-litigation medical negligence dispute settlement is a new breakthrough in the resolution of medical negligence disputes in Indonesia, namely mediation and honors assemblies of the Indonesian medical discipline (MKDKI). Conclusions are needed clear rules regarding medical negligence, medical risk, and medical dispute resolution that must be assessed based on the existing rules so as to produce identical rules based on structure, substance, and culture. Settlement of litigation medical negligence disputes we need to review again. Settlement of mediation medical negligence disputes and MKDKI is an alternative in resolving medical negligence disputes in Indonesia that we must think about for the protection and legal certainty for doctors and patients.Keywords: alternative dispute resolution; medical negligence AbstrakTujuan penelitian yaitu untuk menganasis penyelesaian sengketa kelalaian medik di Indonesia secara litigasi (pidana dan perdata) dan nonlitigasi. Metode penelitian yaitu yuridis normatif. Hasil penelitian adalah penyelesaian sengketa kelalaian medik nonlitigasi merupakan terobosan baru dalam penyelesaian sengketa kelalaian medik di Indonesia yaitu mediasi dan majelis kehormtan disiplin kedokteran Indonesia (MKDKI). Simpulan diperlukannya aturan yang jelas mengenai kelalaian medik, risiko medik, dan penyelesaian sengketa medik yang harus dikaji berdasarkan kaidah-kaidah yang ada sehingga menghasilkan kaidah yang identik berdasarkan struktur, substansi, dan budaya. Penyelesaian sengketa kelalaian medik litigasi perlu kita kaji lagi. Penyelesaian sengketa kelalaian medik mediasi dan MKDKI merupakan alternatif dalam penyelesaian sengketa kelalaian medik di Indonesia yang harus kita pikirkan demi perlindungan  dan kepastian hukum untuk dokter dan pasien.Kata kunci : alternatif penyelesaian sengketa; kelalaian medik